Internet of Things Ontology for Digital Twin in Cyber Physical Systems. - Steinmetz, Charles; Rettberg, Achim; Pereira, Carlos Eduardo; Ribeiro, Fabíola Coelho; Schroeder, Greyce (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2018)
The Digital Twin is one of the most important concepts in the Cyber Physical Systems (CPS) era. It can bring benefits such as simulation, monitoring or management once it joins the physical and the virtual through the Internet of Things. This concept is being adopted more and more in the academia and in the industry, but there is still a lack of methods to define and formalize the representation of the Digital Twin, as for example semantic models. Ontologies are a way of representing knowledge that can be shared between different entities, allowing a common understanding about a information. In this sense, this work proposes an ontology to represent Digital Twin in the context of CPS and embedded systems. These concepts are implemented through a proposed architecture. The proposed ideas are being evaluated with industrial case studies and some of the preliminary results are described in the paper.